Nilai Kemanusiaan dalam Foto Jurnalistik Tentang Erupsi Gunung Agung, Bali, di Kompas.Com - Febriani, Erisa; Syas, Muharnetti (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2020)
This study examines the human values contained in photojournalism on the eruption of Mount Agung, Bali, at Kompas.com The research paradigm used is constructivist, qualitative methodology, and the semiotic analysis method of Roland Barthes’s research model. The results of the study show a photo of the eruption of Mount Agung presented as an illustration of a news text which displays the reality as it is without the effects of manipulation. The meaning of denotation shows the events of monitoring activities, evacuation of affected local residents to temporary shelters, the situation at the said shelters, assistance to refugees, presidential visits to affected sites, and community rituals. The meaning of the connotation that is constructed is the personal human dimension in the form of an expression of concern, anxiety; social dimension in the form of caring and equality, and cultural dimension in the form of surrender and spiritual beliefs.